Significance of Ligand-Anchored Polymers for Drug Targeting in the Treatment of Colonic Disorders - Chaubey, Pramila; Momin, Munira; Sawarkar, Sujata (Frontiers in Pharmacology, 2020)
Targeted drug delivery into the colon is highly desirable for the treatment of variety of bowel diseases such as ulcerative colitis, Crohn’s disease, colonic cancers, local treatment of colonic pathologies, and systemic delivery of protein/ peptide drugs. Conventional colon targeted drug delivery systems lack specificity and release significant amount of drug much prior to reaching to colon. Hence, colon targeting is still an open question for further research to deliver therapeutics efficiently and effectively to the desirable site. Ligand anchored therapy is a powerful and effective pharmaceutical approach to achieve selective drug delivery to pathological cells, for both therapeutic as well as diagnostic purposes, with the advantage of minimal side effects and toxicity. Active drug targeting strategy is based on the discovery of overexpressed receptors on pathological cells, compared to their expression in normal tissues. Further, drug resistance constitutes the one of the major reasons of the failure of chemotherapy and presents a major obstacle for the effective treatment. The reason behind drug resistance is exposure of pathological cells/ pathogens to sub-therapeutic levels of drugs due lack of specificity of therapeutics. Active targeting, specifically taken up by the target cells, can warrant exposure of pathological cells/ pathogens to high drug load at the target and sparing non-target cells hence minimal damage to normal cells and least chance of drug resistance. A variety of ligands have been investigated including folate, transferrin, antibodies, peptides and aptamers. Multiple functionalities can be incorporated into the design of nanocarriers, to enable imaging and triggered intracellular drug release. The present review article focuses on recent advances in ligand anchored therapy and its significance on the development of targeted nanocarriers and will introduce novel concepts such as multi-targeting and multi-functional nanocarriers in the treatment of colonic disorders.